Contribuições da Pedagogia Histórico-crítica sobre a organização escolar e os desafios da materialidade na Educação Básica - Turini, Mateus Henrique (2023)
Faced with all the difficulties brought by the pandemic, the present research is devoted to studying the problem of the school organization seeking answers to the question of what are the structural elements of school organization that allow the school to fulfil its social role. For this, it was necessary to reflect on the concept of education, the role of school education and to check whether the school organization can increase the guarantee of the performance of educational work in school times and spaces. Through historical-dialectical materialism and dialectical analysis of discourse as a research methodology, under the perspective of Historical-critical Pedagogy, performs research in the municipal teaching network of Jaú/SP. The researches allowed to extract from reality the analytical groups of procedural, structural mediation and educational mediation as structural elements of the school organization. From the externalization-objectivation-interiorization dialectic, it defines that the school organization is characterized as the practice carried out by the set of school professionals who perceive the presence and movement of the school in the social reality and enables the procedures and structures necessary to ensure educational mediation with the aim of humanizing individuals in school times and spaces. Finally, it presents a proposal for school organization that enriches the problematization and instrumentalization of teachers in educational mediation and transcends the Taylorist, Fordist, Toyotist and Volvista management forms still present in school management, contributing to the critical overcoming of the challenges of the materiality of educational action in Basic Education.